Cooperation, strategic alliances and internationalization of Colombian university (2014)
This article identifies one of the major trends in higher education today, associated with accreditation of quality, with the prestige of the institutions, with the economic viability of their programs. It is materialized in the existence of contents and updated and innovative teaching methods and the widespread assessment and institutional recognition at the international level. It points out how the emphasis of this internationalization is expressed primarily in the mobility of students and teachers, through cooperation agreements and the development of joint study programs through strategic alliances.